TAX ON ZAKAT ON INCOME TAX: PERCEPTIONS OF MUSLIM TAXPAYERS - Amin, Asbi (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This research explores the impact of halal-haram aspect, understanding of the tax regulations and religiosity has signifikant effect on the perception of Muslim taxpayers towards tax rabate over income zakat payments. Collecting data using a questionnaire instrument in this study type of non-probability sampling method used is judgmental sampling to as many as 97 respondents. Data analysis using the Smart PLS structural equation model. The results of the research are halal-haram aspect, understanding of the tax regulations and religiosity has signifikant effect on the perception of Muslim taxpayers towards tax rabate over income zakat payments.